2021
DOI: 10.3390/foods10040690
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Milk Standardization on Chemical Composition, Fat and Protein Recovery, Yield and Sensory Properties of Croatian PGI Lički Škripavac Cheese

Abstract: The aim of this work was to evaluate the influence of cheese milk standardization on chemical composition, fat and protein recovery, yield and sensory properties of Croatian soft Protected Geographical Indication (PGI) Lički škripavac cheese. Standardization of milk to the casein/fat ratio of 0.7 was carried out by adding skimmed milk powder (SMP) to cheese milk and by skimming part of the milk fat. Results showed that losses of fat by whey were significantly (p < 0.05) lower after Lički škripavac cheese pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In our study, the marine algae supplementation caused not only lower cheese protein contents, but also led to lower recovery ratios in the curd in the MA group compared to the C group. Kalit et al [ 22 ] reported that the recovery of fat and protein were 80.1% and 74.4% in cattle, while others reported that the recovery of fat was 75–79%, and the recovery of protein was 80–81% in goats [ 39 , 40 ]. To the best of our knowledge, these recovery parameters have not been previously evaluated in milk from marine-algae-supplemented goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the marine algae supplementation caused not only lower cheese protein contents, but also led to lower recovery ratios in the curd in the MA group compared to the C group. Kalit et al [ 22 ] reported that the recovery of fat and protein were 80.1% and 74.4% in cattle, while others reported that the recovery of fat was 75–79%, and the recovery of protein was 80–81% in goats [ 39 , 40 ]. To the best of our knowledge, these recovery parameters have not been previously evaluated in milk from marine-algae-supplemented goats.…”
Section: Discussionmentioning
confidence: 99%
“…Percentage of fat recovery (3) and protein recovery (4) in the curd for each batch was calculated as [ 22 ]: Recovery of fat = (% fat in cheese × cheese wt)/(% fat in milk × milk wt) Recovery of protein = (% protein in cheese × cheese wt)/(% protein in milk × milk wt) …”
Section: Methodsmentioning
confidence: 99%
“…A study on Croatian soft cheese also indicated that standardisation of cheese milk to CFR of 0.7 by the addition of NDM increased both actual and moisture‐adjusted yield, whereas both decreased when standardisation was made by fat‐removal (Kalit et al . 2021). Furthermore, actual or moisture‐adjusted yields of Gouda cheese increased by 22 or 19% when milk protein was standardised to 5% at constant fat content but yield efficiency (per kg protein) was lower (Mistry and Pulgar 1996), confirming that increasing the concentration at constant CFR could be a more viable approach.…”
Section: Different Metrics Used For Cheese Milk Standardisationmentioning
confidence: 99%
“…The range of technological methods utilised by producers enables greater flexibility of raw materials and control of the production process. The key objectives of milk composition standardisation are: (i) to minimise processing issues due to seasonal variation; (ii) to have predictable manufacture dynamics; (iii) to obtain a more consistent and higher quality final product; and (iv) to acquire the maximum economic return from the milk components while maintaining product quality (Guinee et al 2006;Kalit et al 2021).…”
Section: Milk Standardisation Protocols For Cheese Manufacturing As A...mentioning
confidence: 99%